Transformation of visual practices in the context of primary urbanization - O. Y. Pavlova, (Ukrainian Cultural Studies, 2019)
The article is devoted to the study of the process of primary urbanization as a context of transformation of visual practices. This implies a long- term perspective of studying the city as a mediator of the great tradition. Folk culture in the process of formation of civilization was differentiated into rural and urban one. The city has become a space for formation of new cultural strategies: comprehension, ordering and management. This required changes in the anthropological model.If visual practices of small traditions were included in the de-differentiated structure of sensual orientations of small culture, the big tradition of urban culture supposed inclusion in the space through contemplation. Thus, the spectacle has received the function of subordinate management, and visual practices have been pulled out of the substratum of human capabilities and received a privileged status in the hierarchy of sensual orientations.For this perspective, methodologically significant is the understanding of the opposition of the city as a village/city, which was formulated as the basic American sociologist R. Sennett. It was he who edited the anthology of the classic essay on urban culture, which offered a classification of the German and Chicago Schools of Urban Studies. This classification itself has become widely recognized and does not cause controversy. Our work will focus on this body of work, which not all are known to domestic researchers of the city. Particularly basic in this context will be the work of representatives of the Chicago School of R. Redfield and M. Singler.The purpose of the article is to study the transformations of visual practices in the process of primary urbanization.The dominant of visual practices of urban space is torn from the unity of sensory orientations of folk culture with its ritualized way of self- government and becomes a way of ordering and managing in the situation of primary urbanization as the basic process of formation of civilization in general. In the process of primary urbanization, the city becomes a medium between: governors and subordinates, man and state, culture (as a small tradition) and civilization (as a large tradition).
Keywords: visual practices, city, primary urbanization, littlel tradition, great tradition, civilization